Permanência e sucessão no meio rural: o caso dos jovens de Santana do Livramento/RS - Raquel Breitenbach; Alessandra Troian (Ciências Sociais Unisinos)
Rural succession has been a problem that has been discussed in the academy, among policymakers and, above all, among family farmers around the world. Young people have shown less and less interest in staying in rural areas, but there has been less interest in sequencing the agricultural activities of their parents. In this sense, recognizing the role of young people in the rural development process, the objective of the present study is to analyze the perspectives of the rural young people of Santana do Livramento / RS about the permanence in the rural environment and the interest in the family succession. The methodology of the study is quantitative, performed through descriptive statistics. Structured questionnaires containing open and closed questions were applied to young people, children of farmers, who attended high school, in a total of59 rural youth, aged between 14 and 19 years. The main results are: young people want to stay in the field and have a greater interest in being managers of the property in greater number than the young ones; young people with less land area are less interested in being succes-sors; emotional and relationship factors prevail in the desire for permanence in the fíeld; obstacles to agricultural labor, difficulties in accessing production units, land scarcity, low autonomy, and the economic pressure exerted by large farms, are the factors that contribute to the exit of rural youth from Santana do Livramento / RS.